1896 Wash. Rev. Stat. 686, ch. 260, § 3910, pt. 5 - (:unkn) unknown (General Publisher, 1896)
To carry on the business of manufacturing gun powder, nitroglycerine or other highly explosive substance, or mixing or grinding the materials therefor, in any building within fifty rods of any valuable building, erected at the time such business may be commenced.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER